Characterizing the Retinoblastoma 1 locus: putative elements for Rb1 regulation by in silico analysis - Hajjari, Mohammadreza; Khoshnevisan, Atefeh; Lemos, Bernardo (Frontiers in Genetics, 2014)
Limited understanding of the Rb1 locus hinders genetic and epigenetic analyses of Retinoblastoma, a childhood cancer of the nervous systems. In this study, we used in silico tools to investigate and review putative genetic and epigenetic elements of the Rb1 gene. We report transcription start sites, CpG islands, and regulatory moieties that are likely to influence transcriptional states of this gene. These might contribute genetic and epigenetic information modulating tissue-specific transcripts and expression levels of the Rb1 gene. The elements we identified include tandem repeats that reside within or next to some identified putative CpG islands near Rb1’s transcriptional start site, and that are likely to be polymorphic among individuals. Our analyses highlight the complexity of this gene and suggest opportunities and limitations for future studies of retinoblastoma, genetic counseling, and the accurate identification of patients at greater risk of developing the malignancy.